2022
DOI: 10.3389/fphy.2022.926609
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Microswimmers Under Confinement With Dissipative Particle (Hydro) Dynamics

Abstract: In this work we study microwimmers, whether colloids or polymers, embedded in bulk or in confinement. We explicitly consider hydrodynamic interactions and simulate the swimmers via an implementation inspired by the squirmer model. Concerning the surrounding fluid, we employ a Dissipative Particle Dynamics scheme. Differently from the Lattice-Boltzmann technique, on the one side this approach allows us to properly deal not only with hydrodynamics but also with thermal fluctuations. On the other side, this appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…By extending the DPD numerical framework described in 55 to include the effects of mass and shape asymmetries, we have demonstrated that hydrodynamic interactions, gravity, and thermal fluctuations are sufficient to capture the dynamics of a range of experimental chemically active colloidal systems. 17,18,20,64 Promisingly, the use of DPD particles to build the overall structure of the microswimmer enables us to access to a range of more complex shapes than those described here, whose formulation would otherwise be either intractable or highly challenging when using other numerical modelling frameworks, or explicitly including chemical fields.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By extending the DPD numerical framework described in 55 to include the effects of mass and shape asymmetries, we have demonstrated that hydrodynamic interactions, gravity, and thermal fluctuations are sufficient to capture the dynamics of a range of experimental chemically active colloidal systems. 17,18,20,64 Promisingly, the use of DPD particles to build the overall structure of the microswimmer enables us to access to a range of more complex shapes than those described here, whose formulation would otherwise be either intractable or highly challenging when using other numerical modelling frameworks, or explicitly including chemical fields.…”
Section: Discussionmentioning
confidence: 99%
“…1b (ref. 55)), properly aligned along the x-and y-axes to ensure a flat repulsive potential interacting with both the solvent and colloid particles via the DPD soft conservative force with a large amplitude F c = 100. 49 The microswimmers motility originates from one central "thruster" particle, which generates the squirmer-type force field experienced by the solvent particles in the spherical shell between the outer surface of the microswimmer (dashed black Nanoscale Paper circle) and R H=4 (dashed black circle and dotted black circle respectively, see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations